2016
DOI: 10.1021/acs.est.5b06371
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate Esters in Indoor Window Films in a Northeastern Chinese Urban Center: Film Growth and Implications for Human Exposure

Abstract: Indoor window film samples were collected in buildings during 2014-2015 for the determination of six phthalate diesters (PAEs). Linear regression analysis suggested that the film mass was positively and significantly correlated with the duration of film growth (from 7 to 77 days). PAEs were detected in all window film samples (n = 64). For all the samples with growth days ranged from 7 to 77 days, the median concentrations of total six PAEs (∑6PAEs) in winter and summer window film samples were 9900 ng/m(2) fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 64 publications
(138 reference statements)
3
51
0
Order By: Relevance
“…35 KM-GAP considers mass transport and chemical reaction of SVOCs partitioning between gas phase, particle surface, and particle bulk, and is based on the kinetic model framework presented by Pöschl et al 36 KM-GAP includes gas-phase diffusion and gas-particle interface transport characterized by a model which includes a sorption layer as well as a quasi-static surface layer, 36 surface and bulk chemical reactions, and bulk diffusion within the layers, as well as condensation, evaporation, and heat transfer. 22,28,37 4,35 However, KM-GAP also lacks a mechanistically sound description of the initial film formation step.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…35 KM-GAP considers mass transport and chemical reaction of SVOCs partitioning between gas phase, particle surface, and particle bulk, and is based on the kinetic model framework presented by Pöschl et al 36 KM-GAP includes gas-phase diffusion and gas-particle interface transport characterized by a model which includes a sorption layer as well as a quasi-static surface layer, 36 surface and bulk chemical reactions, and bulk diffusion within the layers, as well as condensation, evaporation, and heat transfer. 22,28,37 4,35 However, KM-GAP also lacks a mechanistically sound description of the initial film formation step.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…45 Studies of SVOC adsorption onto clean surfaces and onto surfaces which had been exposed to kitchen "grime" for several weeks showed that K s converges toward a similar value for materials covered with an organic film, which suggests that the organic layer exhibits properties that are largely independent of the underlying surface material. To describe the formation of organic films on indoor surfaces (which can grow over months 28 ), adsorption may be augmented by additional processes, including condensation and absorption. 46 Nevertheless, the measurements of K s for clean surfaces suggest that SVOC adsorption occurs over timescales of hundreds of hours, but eventually reaches equilibrium.…”
Section: Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some phthalates have been reported to be detectable in indoor air and dust samples (He et al, 2016;Weschler et al, 2015). In addition, poor ventilation in summer when houses are sealed off from the hot possibly influenced the concentrations of phthalates in room (Huo et al, 2016). Considering the two observations, it seems that more indoor activity, particular during summer, may be plausible to cause heavier phthalates exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone and hydroxyl levels are present as indoor oxidants but their levels can be much reduced compared to outdoor levels, strongly dependent on the rate of air exchange, the nature of reactive surfaces indoors, and levels of direct sunlight . These factors lead to the development of films on indoor surfaces, predominantly organic in nature . Semi‐volatile species readily sorb to impervious surfaces as described by a recent model that predicts rapid initial growth rates of the films, followed by slower growth as the films mature .…”
Section: Introductionmentioning
confidence: 99%